2016
DOI: 10.2478/mspe-02-04-2016
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Effective Inertisation of Self-Heating Places in Goaf of Longwall in Hard Coal Mines

Abstract: Underground fires in coal mines belong to the most common hazards, the exposure to which frequently requires long term and costly rescue operations. It is mainly connected with the specific character of underground excavations which have limited volume. This makes the maximum permissible concentration of harmful gases rapidly exceeded and may also cause changes in air flow direction. The most certain way of improving a safety situation in Polish coal mining industry is taking early prevention steps. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Wang 31 implemented an engineering project on fire prevention by nitrogen injection and concluded that the diffusion radius of nitrogen gas decreases and fluctuates with increasing nitrogen injection intensity. Nikodem 32 replaced the O 2 in the gob of a coal mine with inert gas and demonstrated that inertization effectively mitigates the danger of spontaneous combustion. Tao et al 33 developed a closed mining face to improve the purity of extracted gas and studied the effect of micropores in coal on residual coal spontaneous combustion using low-temperature nitrogen adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Wang 31 implemented an engineering project on fire prevention by nitrogen injection and concluded that the diffusion radius of nitrogen gas decreases and fluctuates with increasing nitrogen injection intensity. Nikodem 32 replaced the O 2 in the gob of a coal mine with inert gas and demonstrated that inertization effectively mitigates the danger of spontaneous combustion. Tao et al 33 developed a closed mining face to improve the purity of extracted gas and studied the effect of micropores in coal on residual coal spontaneous combustion using low-temperature nitrogen adsorption.…”
Section: Introductionmentioning
confidence: 99%